Just an ordinary Jew: A case for Why Paul should be studied within Jewish studies - Larsson, Stefan (Nordisk judaistik, 2018)
The apostle Paul, author of many letters in the New Testament, is often considered to be the father of Christian antisemitism and a staunch opponent of keeping the Torah. This perspective has been shared both by Jews and Christians throughout the centuries, until the late twentieth century. For the last forty years or so, a new paradigm on Paul has taken shape, one where Jewish scholarship and research on ancient Judaism is making a significant difference. The picture of a Second Temple-period Pharisee is emerging, possibly with connections to early forms of Merkabah mysticism. There are no longer any reasons but ‘tradition’ that Paul should not be a part of Jewish studies, and this article gives some of the arguments for this timely re-appropriation of one of the best-known Jews in history.